Abatement Innovation in a Cournot Oligopoly: Emission versus Output Tax Incentives - Naoto Aoyama; Emilson C.D. Silva (Center for Economic Studies and ifo Institute (CESifo), 2016)
This study compares energy and emission taxes used to control pollution and provide incentives for the adoption of an advanced abatement technology in a Cournot oligopoly. We examine multistage games where the government may intervene in order to maximize social welfare by setting an environmental tax rate. When the government intervenes, it levies either an energy tax or an emission tax. We show that the effectiveness of either type of tax depends on the shape of the multiproduct technology. In the absence of economies of scope in the production of energy and abatement, the energy tax reduces pollution but is ineffective in promoting technological change. The emission tax reduces pollution and is effective in promoting technological change for sufficiently small fixed costs of adoption. In the presence of economies of scope, firms may adopt the efficient technology even in the absence of taxation. When taxation is necessary for innovation, both types of taxes are effective. However, the energy tax outperforms the emission tax in terms of innovation incentives.
Keywords: D21; D62; D78; L13; H23; O33; 330; externalities; output taxes; emission taxes; technology adoption; Cournot duopoly